Effect of Cervical Traction verses Strengthening Exercises in patients of Cervical Radiculopathy - Sana Tahir, Arif Ali Rana, Noman Ghaffar, Sajjad Ali Sajjad, Qasim Idrees, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cervical radiculopathy is one of the regularly happened conditions caused by the pressure of nerve roots and manual exercise based recuperation has the key part in its administration. Both the strengthening activities and traction has its adequacy, and the present investigation was intended to evaluate their belongings. Aim: To determine the effects of traction on cervical region verses effects of strengthening exercises in patients diagnosed with cervical radiculopathy. Methods: A total of 20 patients (10 males and 10 females) were arbitrarily chosen and retained into two groups A and B. The inclusion standard was patients who were with diagnosed cervical radiculopathy on physical examination with age ranged 25-50 years. The Group A was treated with cervical traction, while group B was treated with strengthening exercises for 3 weeks. The NDI (Neck Disability Index) and Visual Analogue Scale (VAS) were used to amount and measure the disability and searing pain. To analyze the data SPSS version 21 was used and paired t- test was applied at 95% level of implication to determine the statistical results. Results: Patients in group A showed marked improvement as compare to group B. P-value (0.000) less than 0.05 is considered significant. Conclusion: It is concluded that manual traction is far more operative and effective than strengthening exercises for the management of disability and radicular pain in patients diagnosed with cervical radiculopathy.